ANALISIS KELAYAKAN FINANSIAL USAHA VANILI DI KECAMATAN MORAMO KABUPATEN KONAWE SELATAN - Sabrin . (Fakultas Pertanian Universitas Halu Oleo, 2014)
The purpose of this study was to assess the investment worthiness in terms of financial on vanilla farms in District Moramo South Konawe Regency. Research result shows vanilla farms financially viable on the basis of investment appraisal criteria were obtained: (a) NBCR, NPVdan 1RR obtained greater value than one that is NBCR amounted to 19.266, the NPV of 49.243, and the IUR by 220.06%. This means that the ability of farmers to return capital is high enough, (b) obtained payback period is 4 years (the first year of production), this means that the time required to return the investment fund is shorter than the economic life of the plant. Based on these findings the researcher suggests (a) to shareholders with an interest on vanilla farming in Pudari Jaya village can invest in the business, (b) opportunities and prospects of vanilla farming in Moramo district great enough so the government expected to support the development of vanilla farming especially vanilla treatment. Keywords: financial worthiness, vanilla business, shareholder